PENINGKATAN KOMPETENSI DAN KUALITAS MAHASISWA PGSD MELALUI SEMINAR RPP GUNA MENYUSUN INOVASI MASA ADAPTASI - Destini, Frida; Astuti, Nelly; Hermawan, Jody Setya (LPPM Institut Pendidikan Nusantara Global, 2024)
Based on the results of observations at the PGSD study program at the University of Lampung, there are still many students who do not understand what a Learning Implementation Plan (RPP) is, and how to make a good Learning Implementation Plan (RPP). This activity aims to enable students as the future generation of Indonesian teachers to create and understand what a RPP is. Methods of activities in this socialization or training include lecture methods, question and answer, and giving examples. Quantitatively, this seminar can produce students who are competent and able to organize a series of student learning activities properly and correctly. Meanwhile, qualitatively, this activity was attended by more than 89 PGSD students at Lampung University, Metro campus, and the students felt they had gained the knowledge, skills, and experience they needed. The activities are progressing well but are still not fully able to achieve the previously determined targets. It is necessary to follow up and develop similar training for other programs based on field needs.